The group dynamics sparking social change: how group value in diversity predicts interactions with a deviant - Koudenburg, Namkje; Jans, Lise (Frontiers in Social Psychology, 2023)
Deviants are pivotal to sparking social change but their influence is often hindered by group dynamics that serve to maintain the status quo. This paper examines the influence of a group's value in diversity in deviant's ability to spark social change, with a unique focus on the experience and anticipation of group dynamics that enable minority influence. Hypotheses were tested in three studies (NTotal = 674), which varied in their use of ad-hoc conversation groups or existing friend groups, and whether deviants were newcomers, or existing group members. We demonstrated social influence of a vegan deviant increased to the extent that participants perceived their group to value diversity. Furthermore, group value in diversity related to experienced and anticipated group dynamics that enabled minority influence: decreased conformity pressure, increased attentive listening, and, importantly, an increased search for agreement with the deviant. We discuss the importance of studying group dynamics for understanding what valuing diversity entails.